Contemporary Human Rights Law: A Bibliometric Analysis of the Literature from an Islamic and International Law Perspective - Amri Saputra; Shukri Bin Suparti (ELQONUN: HUKUM KETATANEGARAAN ISLAM, 2025)
This study aims to analyze the development of contemporary literature on human rights law (HAM) from an Islamic and international legal perspective through a bibliometric approach using the R Biblioshiny software. This study uses a bibliometric method with a quantitative analysis of scientific publications obtained from the Scopus database for the period 2020–2025. The collected data includes 1,463 articles from 556 sources with contributions from 2,027 authors, which were then analyzed using performance analysis and science mapping techniques. The results of the analysis show that although the number of publications is quite large, the annual growth rate has decreased by -4.93% and the citation trend tends to weaken, indicating that the academic impact of this research still needs to be improved. Thematically, the study shifts from normative issues such as non-discrimination and self-determination to contemporary global issues such as geopolitical conflict, justice, and international human rights law. The largest contributions come from Western countries, especially the United Kingdom, Australia, and the United States, while participation from Global South countries, including Indonesia, is starting to emerge, although still limited. These findings confirm that human rights studies are not only influenced by normative legal dimensions but are also multidisciplinary and influenced by global realities, thus opening up space for integrating Islamic and international legal perspectives in formulating a more inclusive approach. Therefore, further research is recommended to strengthen international collaboration networks, increase the visibility of publications, and encourage broader involvement from developing countries to build a more representative and contextualized human rights discourse.